STRATEGY MANAGEMENT IMPLEMENTATION IN THE DEVELOPMENT OF ACCREDITATION DEVELOPMENT OF GRADUATE STUDY PROGRAMS IN THE FACULTY OF INTRODUCTION AND EDUCATION SCIENCE IN SYIAH KUALA UNIVERSITY - Putri Amalia Mastura; Amiruddin Amiruddin; Ismail Ismail (Jurnal Ilmiah Mahasiswa Pendidikan Ekonomi, 2019)
Accreditation development can be carried out if every educational organizationimplements the right management strategy. Moving on from these assumptions and the problem of the less ideal application of organizational management today, the authors are interested in conducting research with the aim of describing the process of formulating, implementing, and evaluating management strategies in an effort to develop accreditation of undergraduate study programs. This research is a qualitative descriptive study conducted at Unsyiah FKIP where the subject of the research is the head of the study program. Data collection techniques are done through interviews, observation and documentation study. The results showed that the process of formulating strategic management refers to the vision, mission and goals of each study program which is a fundamental foundation in the preparation of strategies thatwill be taken by each head of study program to achieve the goals of the organization as outlined in a series of activities and programs every study program. The implementation of strategies in the FKIP Unsyiah study program is carried out through a series of activities described through the study program organizational structure, study program funding, study program culture, study program policies, internal and external environmental activities and implementation of strategy management in the effort to develop accreditation. Implementation of evaluation and control strategies in the FKIP Unsyiah study program is carried out in monthly, semester and yearly periods through meeting forums and study program deliberations, observations, supervision from universities (AIMA / AMI), and monitoring conducted by the management of study programs and self-study programs that are published in the study program evaluation report.